2021
DOI: 10.1080/16078454.2021.1965725
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the mechanism of granulocyte colony-stimulating factor (G-CSF) that induces the mobilization of neutrophils

Abstract: Over the past 20 years, granulocyte colony-stimulating factor (G-CSF) has driven the attention of researchers as a therapeutic agent for curing patients suffering from neutropenia. Despite the successful use of G-CSF, it currently requires daily injections, which are inconvenient, expensive, and distressing for children. Therefore, an alternative strategy for using G-CSF for treatment is needed. Understanding the G-CSF structure, expression, mechanism of action, and how it induces neutrophils mobilization is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 77 publications
(94 reference statements)
0
29
0
Order By: Relevance
“…Neutrophil-attracting chemokines, such as CXCL1, CXCL2, or CXCL8, are induced in hypoxic tumor tissue, through the activation of hypoxia-inducible factor 1 (HIF-1α or β) [46,57,71], and support neutrophil migration to the tumor site via CXCR1 and CXCR2 receptors [72]. Moreover, inflammatory cytokines stimulate G-CSF production in TME and further induce the generation of new neutrophils in bone marrow (cancer-related granulopoiesis) [73,74]. Neutrophils, in turn, contribute to cancer-related inflammation, thus promoting angiogenesis and tumor progression (Figure 1).…”
Section: Neutrophils In Cancermentioning
confidence: 99%
“…Neutrophil-attracting chemokines, such as CXCL1, CXCL2, or CXCL8, are induced in hypoxic tumor tissue, through the activation of hypoxia-inducible factor 1 (HIF-1α or β) [46,57,71], and support neutrophil migration to the tumor site via CXCR1 and CXCR2 receptors [72]. Moreover, inflammatory cytokines stimulate G-CSF production in TME and further induce the generation of new neutrophils in bone marrow (cancer-related granulopoiesis) [73,74]. Neutrophils, in turn, contribute to cancer-related inflammation, thus promoting angiogenesis and tumor progression (Figure 1).…”
Section: Neutrophils In Cancermentioning
confidence: 99%
“…Although we included the patients treated with G-CSF to identify neutropenia, the role of G-CSF in neutropenic sepsis is controversial. G-CSF can increase peripheral blood leukocyte and lymphocyte cell counts [ 39 ]. The current guidelines recommend prophylactic use of G-CSF for patients treated with chemotherapy with the risk of developing febrile neutropenia [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…But neutrophilic deficiency leads to poor efficacy of conventional periodontal treatment ( 45 ). Studies have shown that patients with neutropenia have a positive response to human granulocyte colony-stimulating factor (G-CSF) ( 5 , 11 , 44 , 46 , 47 ). The literature has also suggested that HPS-2 patients need hematologic follow-up to identify when G-CSF therapy is needed ( 5 ).…”
Section: Discussionmentioning
confidence: 99%